TEACHER AND STUDENTS’ PERCEPTION TOWARDS THE IMPLEMENTATION OF QUIPPER SCHOOL IN ENGLISH SUBJECT - Rachma, Shevina Yuniar (RETAIN, 2021)
This article aims to present the result of the research done in finding how the implementation of Quipper School in teaching English. Besides, it also investigates the teacher’s and students’ perception towards it. The data was taken using semi-structured interview with one of the English teacher and 12 students of grade XI in academic year 2020/2021. As the result of this study, the implementation of Quipper School in teaching English seen as something good and helpful for the teacher. It provided the material and task that the teacher need so they did not need to make any. Also, both the teacher and students find out the advantages and the disadvantages in using Quipper School as the teaching and learning media.